2013
DOI: 10.1108/edi-02-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

What's in the closet: dress and appearance codes and lessons from sexual orientation

Abstract: Purpose -Dress and appearance codes are often seen as trivial, both because they seem to fit within our notions of how people ought to behave, and because they appear to reflect legitimate employer concerns in running a business. But they are not constructed in a vacuum. They reflect and enshrine societal stereotypes and expectations of women and men and how they look -including assumptions about gender and sexuality and majoritarian norms. As such, they punish anyone who is an outlier by reason of gender, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Our experiences of talking about this research suggest that women's bodies and appearance at work are uncomfortable subjects. Women are judged on job performance and appearance, while men are judged on their work (Brower, ). Such judgements create barriers to women's progress and normalizing in elite roles.…”
Section: Resultsmentioning
confidence: 99%
“…Our experiences of talking about this research suggest that women's bodies and appearance at work are uncomfortable subjects. Women are judged on job performance and appearance, while men are judged on their work (Brower, ). Such judgements create barriers to women's progress and normalizing in elite roles.…”
Section: Resultsmentioning
confidence: 99%
“…In client service, Kari believed female workers act as 'bumpers' who do not get as much 'mud' on themselves as male workers. Therefore, he sometimes envisages how the female candidates he has picked for the shortlist go and 'charm' their clients, which we interpret as probable (hetero)sexualization of female employees (e.g., Brower, 2013;Caven et al, 2013).…”
Section: Assessing Communication Skills By Gesturesmentioning
confidence: 99%
“…Women who consistently exhibit masculine behaviors such as confidence, aggressiveness, and self-assuredness tend to be negatively evaluated in the workplace (Heilman, Block, Martell, & Simon, 1998) and passed over for promotions (Rudman & Glick, 2001;Brower, 2013;Price Waterhouse v. Hopkins, 1989). In one such instance, a woman whose professional and business development skills were widely recognized was denied a promotion due to a perceived lack of interpersonal skillswhich her employer viewed as being a result of her masculine presentation (Brower, 2013). The woman worked in a traditionally male field (accounting) where the presence of masculine behaviors such as assertiveness was required for success, however, her employer insisted upon her displaying traditionally feminine behaviors, dress, and mannerisms.…”
Section: Gender and Professionalismmentioning
confidence: 99%
“…The woman worked in a traditionally male field (accounting) where the presence of masculine behaviors such as assertiveness was required for success, however, her employer insisted upon her displaying traditionally feminine behaviors, dress, and mannerisms. Comments from her employer suggested that she attend "charm school", "dress more femininely", and "wear make-up" (Price Waterhouse v. Hopkins, 1989;Brower, 2013). As gender is read through appearance (Deaux & Lewis, 1984), the remarks about her gender mostly focus on her appearance and dress (Brower, 2013).…”
Section: Gender and Professionalismmentioning
confidence: 99%
See 1 more Smart Citation